Implementasi Faktor Psikologis Aparatur Sipil Negara Terhadap Kebijakan Dinas Lingkungan Hidup Manado - Jericho Danga Pombengir; Joyce Jacinta Rares; Karunia Monika Venicia Kewas; Natalia Cristy Senduk; Zefanya Paskalia Maningkas; Richo Yucho Koyo (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2026)
Psychological factors play an important role in shaping employee behavior, work attitudes, and performance within public organizations. In the context of public service delivery, the effectiveness of organizational performance is influenced not only by structural and administrative aspects but also by employees’ psychological conditions. This study aims to analyze the implementation of psychological factors among Civil Servants (ASN) at the Environmental Service of Manado City using Stephen P. Robbins’ organizational behavior framework. The study employed a qualitative descriptive approach. Data were collected through in-depth interviews, observation, and documentation involving civil servants and organizational stakeholders. The analysis focused on four psychological dimensions, namely motivation, perception, work attitude, and job satisfaction. The findings indicate that the implementation of psychological factors has not been fully optimal. Employee motivation remains largely influenced by external factors, including rewards, recognition, and workplace conditions. Perceptions regarding workload distribution and leadership practices also affect work attitudes and commitment to organizational goals. In addition, communication among employees has not been entirely effective, while task distribution remains uneven across work units, leading to differences in job satisfaction levels. These conditions have implications for employee productivity and the quality of public service delivery. The study concludes that strengthening organizational communication, improving leadership practices, ensuring equitable workload distribution, and developing more effective motivation systems are essential to enhance employee satisfaction and organizational performance. Such efforts are expected to support the achievement of more responsive, efficient, and accountable public services.